Novel role of Egr-1 in nicotine-related neointimal formation - Vazquez-Padron, Roberto I. (Oxford University Press, 2010)
AIMS: The aim of this study was to investigate the mechanisms by which nicotine increases vascular smooth muscle cell (VSMC) proliferation and post-injury neointimal formation. METHODS AND RESULTS: Vascular injury was inflicted in the right iliac artery of nicotine-treated and control rats. Nicotine increased post-injury VSMC proliferation (Ki67(+) cells) and neointimal formation (neointima/media ratio, 0.42 ± 0.23 vs. 0.14 ± 0.07, P= 0.02). To determine the mechanisms by which nicotine exacerbates VSMC proliferation, cultured cells were exposed to nicotine, and signalling pathways leading to cell proliferation were studied. Nicotine activated extracellular signal-regulated kinase (ERK) 1/2 in a dose- and time-dependent manner. The blockade of this signalling axis abolished nicotine-mediated proliferation. Functional nicotinic acetylcholine receptors and Ca(2+) influx were necessary for ERK1/2 activation and nicotine-induced mitogenesis in VSMCs. Downstream to ERK1/2, nicotine induced the phosphorylation of Ets-like gene 1 in a timely co-ordinated manner with the up-regulation of the atherogenic transcription factor, early growth response 1 (Egr-1). The treatment of balloon-injured arteries with a lentivirus vector carrying a short hairpin RNA against Egr-1 abolished the deleterious effect of nicotine on vascular remodelling. CONCLUSION: Nicotine acts through its receptors in VSMC to activate the ERK–Egr-1 signaling cascade that induces cell proliferation and exacerbates post-injury neointimal development.